Auditing Principles: A Systems-Based Approach (Book). - Fess, Philip E.; Meyer, Philip E. (The Accounting Review, 1983)
Reviews the book "Auditing Principles: A Systems-Based Approach," 5th ed., by Howard F. Stettler.